1968
DOI: 10.1111/j.1532-5415.1968.tb00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cerebrovascular Insufficiency Treated With Papaverine

Abstract: A sustained‐release papaverine preparation (Pavavid Plateau Cape) was evaluated for is efficacy in relieving symptoms related to cerebrovascular insufficiency. The overall improvement rate in 37 patients whose ages ranged from 45 to 80 years, was 70 per cent. The most consistent benefit was obtained in patients whose symptoms were caused by cerebral ischemia but who did not show evidence of advanced arteriosclerosis or other cerebral damage. The symptom most frequently relieved was the most disturbing one—loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1971
1971
1994
1994

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although this finding has never been confirmed beyond doubt and McHENRY (1972) demonstrated an increase in regional cerebral blood flow in both healthy and ischemic areas in patients, the notion of the "steal phenomenon" as an inevitable consequence of pharmacogenic cerebral vasodilation greatly influenced clinical-pharmacologic and therapeutic attitudes toward cerebral vasodilation as means of pharmacologic intervention in cerebrovascular disease (HOYER, p. 533, this volume). The therapeutic effect of papaverine in geriatric patients with chronic cerebrovascular disease has been investigated repeatedly (DUNLOP, 1968;SMITH et aI., 1968;RITTER et aI., 1971). Favorable effects in those patients have been reported, but due to the poor design of these studies no conclusions as to the efficacy or nonefficacy of the compound can be drawn.…”
Section: Drugs With Direct Vascular Smooth Muscle Effectsmentioning
confidence: 98%
“…Although this finding has never been confirmed beyond doubt and McHENRY (1972) demonstrated an increase in regional cerebral blood flow in both healthy and ischemic areas in patients, the notion of the "steal phenomenon" as an inevitable consequence of pharmacogenic cerebral vasodilation greatly influenced clinical-pharmacologic and therapeutic attitudes toward cerebral vasodilation as means of pharmacologic intervention in cerebrovascular disease (HOYER, p. 533, this volume). The therapeutic effect of papaverine in geriatric patients with chronic cerebrovascular disease has been investigated repeatedly (DUNLOP, 1968;SMITH et aI., 1968;RITTER et aI., 1971). Favorable effects in those patients have been reported, but due to the poor design of these studies no conclusions as to the efficacy or nonefficacy of the compound can be drawn.…”
Section: Drugs With Direct Vascular Smooth Muscle Effectsmentioning
confidence: 98%
“…We know of only one published report (11) of a controlled study of papaverine in geriatric patients; Stern found that 300 mg of papaverine daily in sustained release form relieved 13 of 15 symptoms (e.g., aggression, excitability, lack of cooperation, and apathy) significantly more effectively than did placebo. Although several reports (12–15) of uncontrolled papaverine studies have appeared in the literature, none showed consistently favorable results. So far as we know, the double‐blind study reported here is the first directly comparing the efficacy and safety of Hydergine and papaverine in geriatric patients.…”
mentioning
confidence: 99%